Implementation of two transdiagnostic interventions based on emotional regulation for professionals who treat alcohol addiction in the Spanish mental health system: A multicenter mixed methods pilot study protocol - María V. Navarro-Haro; Alba Abanades-Morillo; Óscar Peris-Baquero; Verónica Martínez-Borba; Elena Crespo-Delgado; Abel Baquero-Escribano; Laura Masferrer-Boix; Jorge Osma (PLoS ONE, 2025)
Emotional dysregulation has been considered a transdiagnostic factor and an important determinant of craving and relapse in alcohol addiction. Dialectical Behavior Therapy (DBT) and the Unified Protocol (UP) are two transdiagnostic emotional regulation programs with good efficacy in improving alcohol addiction severity. However, an important barrier encountered when implementing evidence-based interventions in drug addiction services is the inadequate training received by professionals. This study aims to evaluate the effect of a dissemination and pilot implementation initiative of DBT and UP among professionals treating alcohol addiction in the national Spanish healthcare system. Methods: The study will be conducted in two phases using a mixed methods design. In phase 1, two 3-day training workshops (DBT and UP; 40 hours total) will be provided by experts to at least 130 healthcare workers from three Spanish regions. Participants will be randomly assigned to receive either DBT or UP training first, followed by the other. The study will include a range of quantitative outcomes including beliefs about alcohol abuse, burnout, self-efficacy, attitudes towards evidence-based interventions, organizational variables, acceptability and intention to use the interventions, barriers to implementation, and knowledge acquisition. The appropriateness of the interventions in real community settings will be qualitatively assessed. In phase 2, at least 30 trained professionals will be randomly assigned to implement DBT or/and UP 3-month group interventions in their workplaces with alcohol addiction patients. Quantitative outcomes will include acceptability, feasibility, appropriateness, fidelity and sustainability of the interventions, barriers to implementation, as well as qualitative descriptions of barriers and facilitators during the implementation process. Discussion: To our knowledge, this is the first study to evaluate a pilot implementation of transdiagnostic psychological interventions based on emotion regulation to treat alcohol addiction. Findings of this study will inform of factors influencing the successful implementation of DBT and UP in community-based addiction services. Trial registration: ClinicalTrials.gov NCT06366100.